A new species of Sonerila (Melastomataceae) from the Western Ghats of India - Murugesan, Maruthakkutty; Ravichandran, Vellingiri; Murugan, Chidambaram (Phytotaxa, 2019)
Sonerila coimbatorensis sp. nov. is described here. The new species is closely allied to S. gadgiliana Ratheesh & Sivad., by its acaulescent habit and the presence of a tuber, but differs in having smaller leaves (1.5–4.5 cm wide) with 3–5 nerves, sparsely glandular petiole, single inflorescence with 1–4 flowers, terete peduncle with 6–18 cm long, pedicel and hypanthium green, petals abaxially with a glabrous midrib and with acuminate apex, style 0.4 cm long and glabrous capsule.